Subjects of Story: Women's Voices and Storytelling in Angela Carter's Nights at the Circus. - A. U. S., Harsha; K. A., Aysha Swapna (IUP Journal of English Studies)
Although women had always been tellers and creators of stories in their various roles within families and communities, their narratives had never received due recognition in the literary canon earlier. It is perhaps in the twentieth century, with the publication of Virginia Woolf's A Room of One's Own, that Anglo-American literature began to seriously regard the possibility of a distinct women's voice in literature. Feminist literary theory observes that traditional literature had mostly given women only the passive object position in its stories, and that the active position of the subject, or the storyteller, had been denied to them. The twentieth century marks a noticeable shift in the trend, with women writers and women's voices gaining more prominence across literary genres. This paper analyzes the patterns of narration and storytelling in the novel Nights at the Circus by well-known twentieth century British writer Angela Carter. Taking into account the views of French feminists Julia Kristeva, Luce Irigaray and Hélène Cixous on women's writings, and Mikhail Bakhtin's concept of polyphonic narrative, this paper argues that Carter, with her distinct polyvocal and intertextual style of narration, writes back to the Western literary canon by placing the marginalized and traditionally othered women's voices in subject-positions, from where they can deliver their own stories and histories.